Becoming an English Teacher: An Autobiographical Narrative Inquiry - Afrianto Daud (AL-ISHLAH: Jurnal Pendidikan, 2021)
This paper documents a fragment of a story in my life that plays a significant role in shaping my identity as an English teacher and influencing me in deciding to become an English teacher as my career choice. This study's research question is 'how and why did I decide to become an English teacher?'. This study was conducted using the "narrative inquiry" method underthe qualitative research paradigm. The study is carried out by describing an individual's life, collecting and retelling parts of his life relevant to the research topic. In this study, the fragments of the story that are retold are the writer's own experience. This study shows that a person's journey to become a teacher can start long before he/she enters a teacher education institution. A person's decision to become a teacher can come internally and come from external factors, such as the influence of 'significant others', socio-cultural factors, economic factors, and teacher political factors. All of these factors are intertwined or influence a person's final decision on whether to choose a career as a teacher or not.